2012
DOI: 10.1161/circulationaha.112.109868
|View full text |Cite
|
Sign up to set email alerts
|

GRK2-Mediated Inhibition of Adrenergic and Dopaminergic Signaling in Right Ventricular Hypertrophy

Abstract: Background The cause and consequences of impaired adrenergic signaling in right ventricular failure/hypertrophy (RVH) are poorly understood. We hypothesized that G protein–coupled receptor kinase-2 (GRK2)–mediated uncoupling of β-adrenergic receptor signaling impairs inotropic reserve. The implications of right ventricular (RV) adrenergic remodeling for inotrope selection and the therapeutic benefit of interrupting Gβγ–GRK2 interaction, using gallein, were tested. Methods and Results Chamber-specificity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 32 publications
(41 reference statements)
5
88
2
Order By: Relevance
“…This might have led to a consistent overestimation of the cardiac output and, thus, of ventricular volumes. However, the observed ventricular volumes in this study are in line with previous reports (21,39). Moreover, the concomitant use of relative increases in volumes (which is not affected by this overestimation) discarded this potential limitation.…”
Section: Limitationssupporting
confidence: 92%
“…This might have led to a consistent overestimation of the cardiac output and, thus, of ventricular volumes. However, the observed ventricular volumes in this study are in line with previous reports (21,39). Moreover, the concomitant use of relative increases in volumes (which is not affected by this overestimation) discarded this potential limitation.…”
Section: Limitationssupporting
confidence: 92%
“…16 ) and found that 6 weeks of pressure overload resulted in enhanced baseline RV contractility while LV baseline contractility remained unaffected. These data are different from the data published by Piao et al [ 19 ]. Piao, Archer, and collaborators showed that 4 weeks after PAB, the CO and treadmill distance were signifi cantly reduced in the PAB versus control animals.…”
Section: Pulmonary Artery Bandingcontrasting
confidence: 97%
“…Bogaard et al 18 demonstrated that treatment with the nonselective adrenergic blocker carvedilol improved maladaptive RVH functionally and histologically without affecting the lung circulation, and similar effects have been demonstrated utilizing other adrenergic receptor blockers. 19 More recently, Piao et al 12 evaluated the role of adrenergic desensitization in RVF and demonstrated that G protein-coupled receptor kinase 2 mediated an uncoupling of β-adrenergic receptor signaling, therefore impairing inotropic reserve. A particularly interesting finding from this study is that, at least in rats, downregulation of the β1, α1, and dopamine 1 receptors was partially independent of pressure overload.…”
Section: The Lung Circulation-rv Axismentioning
confidence: 99%